Iterative algorithm to calculate square and cubic roots for secondary and high school students: Algoritmo iterativo para calcular raíces cuadradas y cúbicas para estudiantes de educación media - Sandoval Hernández, Mario A. (2025)
This article introduces a teaching method using the Newton-Raphson numerical algorithm, specifically designed to teach high school students in Mexico how to compute square and cubic roots. The method relies on the Newton-Raphson algorithm’s quadratic convergence stopping criterion, which achieves precision up to four significant digits in the roots calculated within just two iterations. Additionally, factor decomposition supports the application of this methodology. The article also includes numerical examples commonly given to middle school students, providing them with practical experience in using the algorithm as it is taught in secondary and high schools. Applying this algorithm helps enhance students’ mental arithmetic skills, offering a significant educational benefit.